Moral Elevation and Economic Games: The Moderating Role of Personality - Pohling, Rico; Diessner, Rhett; Stacy, Shawnee; Woodward, Destiny; Strobel, Anja (Frontiers in Psychology, 2019)
Moral elevation is the prototypical emotional response when witnessing virtuous deeds of others. Yet, little is known about the role of individual differences that moderate the susceptibility to experiencing this self-transcendent emotion. The present experiment investigated the role of personality traits as moderators of elevation and its behavioral effects using economic games as a measure for prosocial behavior. One aim was to replicate prior findings on trait Engagement with Moral Beauty as moderator for experimentally induced state elevation. A second aim was to explore new potential moderators that were found to be connected to the moral realm: Honesty-Humility, Agreeableness vs. Anger, and Need for Cognition. Third, the present study is among the few investigating the effects of elevation on different prosocial actions and intentions. A sample of US American college students (N = 144) was randomly assigned to either watch a morally uplifting or a humorous video clip. Afterwards, all participants played a dictator game and an ultimatum game, and were asked to volunteer in another time-consuming experiment. In line with our hypotheses, experimentally induced state elevation promoted prosocial behavior, however, only within the dictator game. Also in line with our hypotheses, higher levels of Need for Cognition and higher levels of Engagement with Moral Beauty (but not higher levels of Honesty-Humility and Agreeableness vs. Anger) increased prosocial behavior within the experimental group. In contrast to our hypotheses, none of the investigated personality traits moderated the proneness to experience the state of elevation after seeing an elevating video clip; only the behavioral consequences of elevation were moderated. Our results replicate and extend prior findings on moderators for elevation and exemplify the importance of investigating the role of personality traits in the context of the moral elevation phenomenon.